The GREATS H β + [O iii] luminosity function and galaxy properties at z ∼ 8: walking the way of JWST. Issue 2 (4th April 2019) - De Barros, S; Oesch, P A; Labbé, I; Stefanon, M; González, V; Smit, R; Bouwens, R J; Illingworth, G D
ABSTRACT: The James Webb Space Telescope will allow to spectroscopically study an unprecedented number of galaxies deep into the reionization era, notably by detecting [O iii ]λλ4959, 5007, and H β nebular emission lines. To efficiently prepare such observations, we photometrically select a large sample of galaxies at z ∼ 8 and study their rest-frame optical emission lines. Combining data from the GOODS Re-ionization Era wide-Area Treasury from Spitzer (GREATS) survey and from HST we perform spectral energy distribution (SED) fitting, using synthetic SEDs from a large grid of photoionization models. The deep Spitzer /IRAC data combined with our models exploring a large parameter space enables to constrain the [O iii ] + H β fluxes and equivalent widths for our sample, as well as the average physical properties of z ∼ 8 galaxies, such as the ionizing photon production efficiency with (ξ _ion/erg^-1Hz)25.77 . We find a relatively tight correlation between the [O iii ] + H β and UV luminosity, which we use to derive for the first time the [O iii ]λλ4959, 5007 + H β luminosity function (LF) at z ∼ 8. The z ∼ 8 [O iii ] + H β LF is higher at all luminosities compared to lower redshift, as opposed to the UV LF, due to an increase of the [O iii ] + H β luminosity at a given UV luminosity from z ∼ 3 to z ∼ 8. Finally, using the [O iii ] + H β LF, we make predictions for JWST /NIRSpec number counts of z ∼ 8 galaxies. We find that the current wide-area extragalactic legacy fields are too shallow to use JWST at maximal efficiency for z ∼ 8 spectroscopy even at 1 h depth and JWST pre-imaging to ≳30 mag will be required.